SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Combined reduced expression of two gene families lowers nicotine content to ultra-low levels in cultivated tobacco - Sheri P. Kernodle; Sydney Webb; Tyler M. Steede; Ramsey S. Lewis (Plant Cell Reports, 2022)

Groundwater as a source of dissolved organic matter to coastal waters: Insights from radon and CDOM observations in 12 shallow coastal systems - Jackie R. Webb; Isaac R. Santos; Damien T. Maher; Douglas R. Tait; Tyler Cyronak; Mahmood Sadat‐Noori; Paul Macklin; Luke C. Jeffrey (Limnology and Oceanography, 2019)
The influence of groundwater and pore‐water exchange on dissolved organic matter (DOM) dynamics in coastal surface waters remains poorly understood. Here, we combine bottom up (i.e., groundwater‐derived flux estimates) and top down (i.e., water column response) evidence to assess whether groundwater exchange drives DOM dynamics in shallow coastal waters. We rely on automated chromophoric DOM (CDOM, a proxy for DOM) and radon ( 222 Rn, groundwater proxy) measurements over tidal time scales in 12 shallow systems, including tidal freshwater wetlands, estuaries, mangroves, coral reefs, coastal lakes, a saltmarsh, and a residential canal estate. Groundwater‐derived dissolved organic carbon (DOC) fluxes ranged from 2 ± 2 mmol m −2 d −1 in a coral reef to 1941 ± 1325 mmol m −2 d −1 in a mangrove tidal creek. These groundwater fluxes replaced surface water DOC inventories on time scales ranging from ~ 0.5 d to several weeks. Systems with short replacement times displayed positive correlations between radon and CDOM in surface waters. Groundwater exchange diluted surface water DOC in four systems. Using multiple lines of evidence, we interpreted groundwater to be an important source of DOM to surface waters in 4 out of the 12 systems, including an offshore coral reef lagoon with low surface water DOC concentrations. Groundwater discharge was a negligible source of DOM in systems with high surface water DOC and CDOM concentrations such as tidal freshwater wetlands and coastal lakes. This investigation highlights the high variability in groundwater‐derived DOC fluxes and responses in the water column, and demonstrates that submarine groundwater discharge and advective pore‐water exchange should be considered in coastal carbon budgets.

Human Neural Stem Cell Extracellular Vesicles Improve Tissue and Functional Recovery in the Murine Thromboembolic Stroke Model - Robin L. Webb; Erin E. Kaiser; Shelley L. Scoville; Tyler A. Thompson; Sumbul Fatima; Chirayukumar Pandya; Karishma Sriram; Raymond L. Swetenburg; Kumar Vaibhav; Ali S. Arbab; Babak Baban; Krishnan M. Dhandapani; et al. (Translational Stroke Research, 2018)

Erratum to: Anti-CarP antibodies as promising marker to measure joint damage and disease activity in patients with rheumatoid arthritis - Alvin Yee; Tyler Webb; Andrea Seaman; Maria Infantino; Francesca Meacci; Mariangela Manfredi; Maurizio Benucci; Gabriella Lakos; Ennio Favalli; Tommaso Schioppo; Pier-Luigi Meroni; Michael Mahler (Immunologic Research, 2015)

Anti-CarP antibodies as promising marker to measure joint damage and disease activity in patients with rheumatoid arthritis - Alvin Yee; Tyler Webb; Andrea Seaman; Maria Infantino; Francesca Meacci; Mariangela Manfredi; Maurizio Benucci; Gabriella Lakos; Ennio Favalli; Tommaso Shioppo; Pier-Luigi Meroni; Michael Mahler (Immunologic Research, 2015)

Extensive gaps and biases in our knowledge of a well‐known fauna: implications for integrating biological traits into macroecology - Elizabeth H. M. Tyler; Paul J. Somerfield; Edward Vanden Berghe; Julie Bremner; Emma Jackson; Olivia Langmead; Maria Lourdes D. Palomares; Thomas J. Webb (Global Ecology and Biogeography, 2012)
Aim Ecologists seeking to describe patterns at ever larger scales require compilations of data on the global abundance and distribution of species. Comparable compilations of biological data are needed to elucidate the mechanisms behind these patterns, but have received far less attention. We assess the availability of biological data across an entire assemblage: the well‐documented demersal marine fauna of the United Kingdom. We also test whether data availability for a species depends on its taxonomic group, maximum body size, the number of times it has been recorded in a global biogeographic database, or its commercial and conservation importance. Location Seas of the United Kingdom. Methods We defined a demersal marine fauna of 973 species from 15 phyla and 40 classes using five extensive surveys around the British Isles. We then quantified the availability of data on eight key biological traits (termed biological knowledge) for each species from online databases. Relationships between biological knowledge and our predictors were tested with generalized linear models. Results Full data on eight fundamental biological traits exist for only 9% ( n = 88) of the UK demersal marine fauna, and 20% of species completely lack data. Clear trends in our knowledge exist: fish (median biological knowledge score = six traits) are much better known than invertebrates (one trait). Biological knowledge increases with biogeographic knowledge and (to a lesser extent) with body size, and is greater in species that are commercially exploited or of conservation concern. Main conclusions Our analysis reveals deep ignorance of the basic biology of a well‐studied fauna, highlighting the need for far greater efforts to compile biological trait data. Clear biases in our knowledge, relating to how well sampled or ‘important’ species are suggests that caution is required in extrapolating small subsets of biologically well‐known species to ecosystem‐level studies.